Omnipotence - Wreen, Michael J. (International journal for philosophy of religion, 2018)
If asked to define 'omnipotence,' the man on the street would probably say that it's the ability to do anything. That's about it, he'd think; nothing more needs be said. Philosophers are never so easily satisfied. They take it as matter of professional duty to find serious problems in important concepts, and to suggest that the concept be rejected or that solutions are at hand. This paper falls into the latter camp. Beginning with a relatively simple definition of 'omnipotence,' increasingly complex definitions are proposed, problems are found with them, and newer, refined definitions are offered. In all, seven unsatisfactory definitions are examined before an adequate one is arrived at. Both traditional and new problems are addressed, and novel solutions are advanced. The definition argued to be adequate is itself novel, but also very much in keeping with our pre-reflective understanding of omnipotence. On the basis of the definition it's concluded not only that an adequate definition of 'omnipotence' is possible, but that various problems alleged to attend attributing the notion to God can also be solved.